2021
DOI: 10.3390/horticulturae7040065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Analysis of Tomato (Solanum lycopersicum L.) with Morphological, Cytological, and Molecular Markers under Heat Stress

Abstract: Tomatoes are usually consumed daily in the human diet. High temperatures reduce the number of tomato yields per year. Heat stress has been considered one of the most prominent causes of alterations in morphological and molecular characteristics in crops that decrease normal growth, production, and yield in diverse plants, including tomatoes (Solanum lycopersicum L.). In this study, we evaluated six tomato lines, namely G1, G2, G3, G4, G5, and G6, at morphological, molecular, and cytological levels under heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The most important aims in cytogenetic investigations are chromosome identification and karyotype study. In the cytological examination, karyotype study is vital for demonstrating origin, polidy, chromosome attributes, and taxonomic and phylogenetic relationships between plants ( Eroğlu et al, 2013 ; Akbar et al, 2020 ; EL-Mansy et al, 2021 ). Karyoevolutionary forms are illustrated and demonstrated by studying karyotype attributes and their formula ( Weiss-Schneeweiss et al, 2013 ; Soliman et al, 2019 ; Soliman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important aims in cytogenetic investigations are chromosome identification and karyotype study. In the cytological examination, karyotype study is vital for demonstrating origin, polidy, chromosome attributes, and taxonomic and phylogenetic relationships between plants ( Eroğlu et al, 2013 ; Akbar et al, 2020 ; EL-Mansy et al, 2021 ). Karyoevolutionary forms are illustrated and demonstrated by studying karyotype attributes and their formula ( Weiss-Schneeweiss et al, 2013 ; Soliman et al, 2019 ; Soliman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato ( Solanum lycopersicum L.) is one of the most relevant productions of the agro‐horticultural sector in not just Ethiopia but also around the world (El‐Mansy et al., 2021; Tolessa et al., 2013; Worku & Sahe, 2018) for its edible fruits. This nutritious fruit is a valuable vegetable which could be taken raw as salad, processed as puree, ketchup, juice, or powder, and cooked as tomato sauce or soup which has been reported to be an effective remediation for sufferers of constipation (Alda et al., 2009; Rehman et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers were interested in the natural phenotypic variations which positively affect natural morphological diversity and genetic variations in a diverse population [3,27]. In this study, the analysis of variance for all the morphological characters showed a wide range of variation among tomato accessions, including fruit shape-related perimeter, fruit shape index, curved fruit shape index, and fruit shape index internal.…”
Section: Morphological Characteristicsmentioning
confidence: 91%
“…These insights have provided the breeders with new knowledge and tools for plant improvement and the ability to detect the variation between species, varieties, and accessions; for example, using several types of DNA molecular markers can be used such as random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP), minisatellites, variable number of tandem repeats (VNTRs), and simple sequence repeats (SSRs) [11,[19][20][21]. SSRs are sections of DNA consisting of (1)(2)(3)(4)(5)(6) or (2)(3)(4)(5)(6)(7) base pair units tandemly repeated throughout the genome [20,[22][23][24], to detect the variation degree [9,21,24] or phylogenetic [25][26][27]. The hypervariability character of SSR markers, based on microsatellite DNA loci, enables this method to be the main major in studying plant population genetics [8,20,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%